Analisis Pelaksanaan Sistem Informasi Manajemen Puskesmas (Simpus) Dalam Menunjang Standar Pelayanan Minimal Kesehatandi Puskesmas Kamonji Kota Palu Provinsi Sulawesi Tengah - Idris, Idris (Jurnal Bidan Cendrawasih Palu, 2019)
This Research aim to : To analyse execution of Information System Management of Puskesmas (SIMPUS) At Input phase, Process, and Output in Puskesmas Kamonji, Palu Regency, Central Sulawesi Province.The research was qualitative research that having the character of exploration with approach of system (input, process, and output) to execution of Information System Management of Puskesmas (SIMPUS) Informant Research is components in concerned in execution of SIMPUS in Puskesmas covering head of puskesmas and organizer of program of SIMPUSin Puskesmas. Informan determined intentionally (sampling purposive) that is Head of Puskesmas and of KTU or underwriter answer SIMPUS which have taken hold of more than 1 year. Result of research indicate that 1) At input system sub, management processing of program of SIMPUSin Puskesmas Kamonji, leadership of head of Puskesmas with authority delegation, and still to the number of officer which is indigent exploit facility / computer in working [him/ it] so that program execution of SIMPUS in Puskesmas Kamonji not yet yielded an performance matching with harapan.2) At process system sub, gathering, processing and presentation of data not yet earned to be executed better because lack of skill and commitment also the limited energy so that do not support in execution of program of SIMPUS. Suggestions for achieving satisfactory performance, all SIMPUS officers can take part in training programs so that in carrying out their duties they can work with great self-motivation to produce good performance.